Analisis Perbandingan Sistem Hukum Pidana di Indonesia dengan Malaysia terhadap Kejahatan Tindak Pidana Korupsi - Sigit Kamseno (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research uses a normative juridical method by comparing criminal law arrangements related to corruption crimes enacted in two countries, namely Indonesia and Malaysia. This is motivated by the issue of corruption in both countries which is still a big problem, even though in terms of the Corruption Achievement Index (CPI), Malaysia is much better than Indonesia. From the results of the research, it is found that there are similarities and differences in the arrangements related to corruption crimes in the two countries. The similarities in both Indonesia and Malaysia are the implementation of the reverse proof system and the establishment of a special institution to eradicate corruption. While the difference is that Indonesia has more legal regulations, the existence of special courts for corruption crimes and the best evidentiary system is applied generally to every form of corruption crime. Meanwhile, Malaysia only has one legal regulation, does not have a special court for corruption and the reverse proof system applied is only limited to bribery cases. From these differences, it can be seen that in terms of the legal system and handling of corruption crimes, Indonesia is better than Malaysia.